ENHANCING COAL SUPPLY PERFORMANCE THROUGH LEAN COAL FLOW AND STOCKPILE CAPACITY OPTIMIZATION - Dian Lazuardy Bachtiar Ardaraja; Yuanita Handayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study evaluates the coal supply operations at a mine-mouth power plant that faces operational challenges due to increasing production and fluctuating demand, which have led to limited stockpile capacity and inefficient coal flow. By integrating safety stock analysis, livestock capacity planning, and lean management principles, the research identifies that the current fixed safety stock benchmark of 100,000 tons will be insufficient by 2027, requiring an increase to 171,194 tons/month to maintain a 95% service level. The findings reveal that the existing livestock capacity of 230,000 tons is inadequate for future needs, necessitating an expansion to approximately 764,108 tons to accommodate rising throughput and eliminate the need for costly temporary stockpiles and double handling. Implementing these structural improvements and reconfiguring the system to a direct coal flow is projected to reduce hauling distances by 0.6 km per ton, resulting in substantial operational cost savings of approximately Rp317.5 billion per year until 2027. Ultimately, this research provides an integrated framework that demonstrates how aligning physical infrastructure with lean principles can achieve sustainable economic benefits and ensure a more reliable coal supply chain.